TiO2/ZnO-based composite thin films coated on FTO surface by screen printing method: increasing dye-sensitized solar cell performance - Demir, Abdullah; Aslan, Fehmi; Esen, Hikmet (Springer, 2024)
This study examined the impact of hydrothermally synthesized TiO2:ZnO composite-based nanopowders on the efficiency of dye-sensitized solar cells (DSSCs). Pure TiO2, 3TiO(2):1ZnO, 1TiO(2):1ZnO, 1TiO(2):3ZnO, and pure ZnO thin films were coated on the conductive glass surface by the screen printing method. XRD and SEM were used to examine the thin film's surface photographs and crystal structure, respectively. XRD analyses confirmed the formation of targeted crystal phases in the structure. It was understood from SEM studies that the TiO2:ZnO composite structure was formed successfully. I-V characterization results showed that the cell combined with the composite 3TiO(2):1ZnO electrode had the highest power conversion efficiency (9.9%). In addition, it was determined from EIS analysis that interfacial charge transfer occurred more efficiently in cells with high TiO2 ratio.
Keywords: Nanoparticles; Photoanodes; Nanoflower; Electrode